Mutation in mitochondrial ribosomal protein MRPS22 leads to Cornelia de Lange-like phenotype, brain abnormalities and hypertrophic cardiomyopathy - Smits, Paulien; Saada, Ann; Wortmann, Saskia B.; Heister, Angelien J.; Brink, Maaike; Pfundt, Rolph; Miller, Chaya; Haas, Dorothea; Hantschmann, Ralph; Rodenburg, Richard J. T.; Smeitink, Jan A. M.; van den Heuvel, Lambert P. (European journal of human genetics, 2011)
The oxidative phosphorylation (OXPHOS) system is under control of both the mitochondrial and the nuclear genomes; 13 subunits are synthesized by the mitochondrial translation machinery. We report a patient with Cornelia de Lange-like dysmorphic features, brain abnormalities and hypertrophic cardiomyopathy, and studied the genetic defect responsible for the combined OXPHOS complex I, III and IV deficiency observed in fibroblasts. The combination of deficiencies suggested a primary defect associated with the synthesis of mitochondrially encoded OXPHOS subunits. Analysis of mitochondrial protein synthesis revealed a marked impairment in mitochondrial translation. Homozygosity mapping and sequence analysis of candidate genes revealed a homozygous mutation in MRPS22, a gene encoding a mitochondrial ribosomal small subunit protein. The mutation predicts a Leu215Pro substitution at an evolutionary conserved site. Mutations in genes implicated in Cornelia de Lange syndrome or copy number variations were not found. Transfection of patient fibroblasts, in which MRPS22 was undetectable, with the wild-type MRPS22 cDNA restored the amount and activity of OXPHOS complex IV, as well as the 12S rRNA transcript level to normal values. These findings demonstrate the pathogenicity of the MRPS22 mutation and stress the significance of mutations in nuclear genes, including genes that have no counterparts in lower species like bacteria and yeast, for mitochondrial translation defects.
online veröffentlicht 29 December 2010
Gesehen am 18.10.2022